Multicultural Literacy Development Strategy in Basic Education Curriculum in Indonesia - Nabilah, Salmi Harfi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
Multicultural literacy is becoming increasingly important in today's globalized world, particularly in diverse societies like Indonesia. This paper explores strategies for developing multicultural literacy in the basic education curriculum of Indonesia. Employing qualitative methods, this study conducts a comprehensive literature review and library research to examine existing frameworks, policies, and practices related to multicultural education in Indonesia's basic education system. The research identifies key challenges and gaps in the current curriculum and proposes strategies to enhance multicultural literacy among students. The study underscores the significance of incorporating diverse cultural perspectives, histories, and values into the curriculum to foster empathy, respect, and understanding among students from different ethnic, religious, and socio-economic backgrounds. Furthermore, the paper highlights the need for teacher training programs to equip educators with the necessary knowledge, skills, and pedagogical approaches to effectively implement multicultural education in the classroom. The findings suggest the importance of integrating multicultural literacy across various subjects and learning activities to promote inclusive learning environments and prepare students for active citizenship in a multicultural society. The proposed strategies aim to address the complexities of cultural diversity and promote social cohesion and harmony in Indonesian schools. Overall, this research contributes to the ongoing discourse on multicultural education and offers practical insights for policymakers, educators, and curriculum developers in Indonesia and other diverse societies.